The role of educational institutions in globalising language towards sustainable hospitality/tourism development - Gallato, Cristina G.; Reamillo, Kristy Aireen Gallato; Warokka, Ari; Abdullah, Haim Hilman (Inderscience Publishers, 2012)
In this paper, we address the issue of globalising language in the hospitality/tourism industry, as one of the key ingredients of sustainable development. English is and has been considered as the lingua franca of business, which is acceptable worldwide, and thus, it needs to be promoted as the medium of communication especially in the tourism/hospitality industry. Travelers/tourists often prefer to visit a country where communication is not a problem.Unfortunately, the language barrier is still one of the priority concerns of the hospitality/tourism industry, particularly in some Asian non–English speaking countries.A home/hotel/restaurant/tourist spot/school/office/village/nation that is friendly communication–wise has always that charm of enticing visitors/guests to come back.Guests that keep on coming back imply repeat business, which ultimately would add figures into the bottom line. Globalising language may help to eliminate the issue of language barriers, and thus help to promote the hospitality/tourism industry.